Transformasi Museum Ki Pahare : Peran Dalam Pelestarian Budaya Dan Pembelajaran Sejarah Di Sukabumi (2016 – 2024) - Akmal Avisena, Muhammad (TAMADDUN, 2024)
ABSTRACT Ki Pahare Museum Sukabumi, as a cultural institution that focuses on preserving local traditions and history education, has undergone significant transformation between 2016 and 2024. This study aims to examine the changes that have occurred at Ki Pahare Museum, from physical changes to managerial innovations, and their impact on cultural preservation and history learning in Sukabumi. The museum was born from the initiative of a local community with a strong dedication to the preservation of Sundanese history and culture, with a collection that includes historical artifacts, traditional tools, and colonial photo documentation. During its development, the museum faced challenges, including a change in location due to government policy, but managed to adapt and remain relevant amidst social and cultural changes. The results show that Ki Pahare Museum is not only a storage center for historical artifacts, but also a symbol of adaptive cultural preservation in the midst of modernization. The museum is committed to strengthening local identity, establishing partnerships with educational institutions, and continuing to develop as a relevant institution in cultural preservation and historical education